Diffusion of Disruptive Innovation in Islamic Primary Education: Implementation of Smart Teacher AI for Digital Competence Development - Novriyanto, Erwin; Hardhienata, Soewarto (PPSDP International Journal of Education, 2025)
This study explores the diffusion of disruptive innovation in Islamic primary education through the implementation of Smart Teacher AI, an AI-driven professional learning platform designed to strengthen teachers’ digital competence. The research employs a Research and Development (R&D) approach based on Borg and Gall’s model, focusing on the implementation phase of Smart Teacher AI in SD Islam Al Ittihad, Cibubur. Data were collected from 25 teachers using observation sheets, digital competence rubrics, focus group discussions, and system usage analytics. The findings reveal that the implementation of Smart Teacher AI aligns with Rogers’ diffusion of innovation framework, showing gradual adoption from innovators to early and late adopters. The platform significantly improves teachers’ digital skills in lesson planning, designing interactive learning media, and evaluating digital learning outcomes. The novelty of this study lies in integrating AI-assisted professional learning within the framework of Islamic values, bridging the gap between technological disruption and faith-based education. The results contribute to both theoretical and practical insights on innovation diffusion in education, emphasizing that digital transformation in Islamic schools requires not only technology readiness but also value-driven leadership and sustainable pedagogical adaptation.